On the (geo)politics of belonging: Agamben and the UN Declaration on the Rights of Indigenous Peoples. (1st October 2016) - Rifkin, Mark
ABSTRACT: This essay considers the significance of the UN Declaration on the Rights of Indigenous Peoples (UNDRIP), drawing on the work of Giorgio Agamben in order to do so. UNDRIP provides means for developing a comparative framework for conceptualizing the situation of Indigenous peoples globally, focusing on the ways they defy settler-state norms and expectations of what constitutes politics and governance. Reciprocally, the essay addresses how UNDRIP reframes Agamben's notion of exception by emphasizing less the eradication of sovereignty than the recognition of simultaneous, interlacing sovereignties whose terms may not be commensurate and whose nonexclusivity troubles a notion of jurisdictional closure – the a priori coherence of 'domestic' space on which the exception depends.